1981
DOI: 10.1111/j.1365-2427.1981.tb01269.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and recession of aquatic macrophytes on an unshaded section of the River Lambourn, England, from 1971 to 1976

Abstract: Freshwater Biology i\9S]) n, Growth and recession of aquatic niacrophytes on an unshaded section of the River Lamhourn, England, from 1971 to 1976 SUMMARY. The growth and recession of the macrophytes on an unshaded f section of the R. Lamboum was documented by a mapping procedure from March 1971 to December 1976. The seasonal patterns were determined mainly by the dominant macrophytes. RanututUiis penicillalns var. calcareus and Ranuncultis peltatiis. Ranunculus grew rapidly in spring and early summer, mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 9 publications
3
38
1
Order By: Relevance
“…Our estimated values of macrophyte standing crop over a cycle of growth and recession were within the seasonal ranges reported in other studies of the chalk river macrophyte community (Dawson, 1976;Ham et al, 1981;Armitage and Cannan, 2000;Flynn et al, 2002). Percentage cover, percentage volume, and dry weight 8 biomass co-varied in accordance with our first hypothesis, concordant with previous studies which had reported positive relationships (O'Hare et al, 2010b;Yin et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Our estimated values of macrophyte standing crop over a cycle of growth and recession were within the seasonal ranges reported in other studies of the chalk river macrophyte community (Dawson, 1976;Ham et al, 1981;Armitage and Cannan, 2000;Flynn et al, 2002). Percentage cover, percentage volume, and dry weight 8 biomass co-varied in accordance with our first hypothesis, concordant with previous studies which had reported positive relationships (O'Hare et al, 2010b;Yin et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Although biomass and cover do not necessarily show a simple linear relationship (Dawson, 1976), percentage cover is also considered as a good measure of plant abundance too (Kershaw, 1973 ;Ham et al, 1981), and is easier to evaluate . The sampling method used the cover scale of Braun-Blanquet (1932) but, because of the non-linear nature of this scale, it was necessary to convert it into cover percentages for the statistical analysis .…”
Section: Discussionmentioning
confidence: 99%
“…B. erecta and H. vulgaris present both vegetative and sexual reproduction but it seems that they have fewer competitive abilities than other species . Furthermore, B. erecta does not generally show regular growth patterns but often increases at times of the year when other species are in recession (Ham et al, 1981 ;Ham et al ., 1982), and this can explain that it did not occur at the same period as the good colonizers, and did not reestablish rapidly after a disturbance .…”
Section: Discussionmentioning
confidence: 99%
“…For the study of small scale pattem, and also for succession, several methods have been used, for example the very precise study of Jones (1955) mapping individual plants, or the studies of Ham et al (1981Ham et al ( , 1982 and Wiegleb (1983) also referring to small sample plots and using more precise estimation methods.…”
Section: Historical and Methodological Outunementioning
confidence: 99%
“…(a) Intensive studies that follow the variation of vegetation within a year and from year to year (Wiegleb 1983, Ham et al 1981, Ham et al 1982 General prineiples of ehange, whieh were supposed by Segal (1971) based on his observation in Duteh waters, eannot be realized. Exaet eauses for the observed ehanges ean only be given in ease of intensive study.…”
Section: Dynamics Of River Vegeta Tionmentioning
confidence: 99%